2005
DOI: 10.3928/01484834-20050601-05
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Self While Learning to Care for Others: A Challenge for Nursing Students

Abstract: While learning to care for others, undergraduate nursing students often fail to care for themselves. This study examined the effect of a self-care intervention on undergraduate nursing students. Self-care is the practice of health-related activities in which individuals engage to adopt a healthier lifestyle. A pretest-posttest, single group design was used to test whether students increased their self-care activities after completing a course requiring self-care. Full-time junior nursing students ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 13 publications
5
36
0
2
Order By: Relevance
“…In a study conducted in Mexico, it was found that students in the age group 17-24 have higher score average in physical activity, stress management and interpersonal support sub-scales parallel to our findings compared to students at the age of 25 and older [25]. In another study done in America, it was found that student at an older age have higher scores in scale total score and health responsibility sub-scale [26]. Different from our findings, there is a study where there is no statistically significant difference in healthy lifestyle behavior scale total [30].…”
Section: In Terms Of Different Age Groupssupporting
confidence: 86%
See 1 more Smart Citation
“…In a study conducted in Mexico, it was found that students in the age group 17-24 have higher score average in physical activity, stress management and interpersonal support sub-scales parallel to our findings compared to students at the age of 25 and older [25]. In another study done in America, it was found that student at an older age have higher scores in scale total score and health responsibility sub-scale [26]. Different from our findings, there is a study where there is no statistically significant difference in healthy lifestyle behavior scale total [30].…”
Section: In Terms Of Different Age Groupssupporting
confidence: 86%
“…In a study conducted among university students in Mexico, the order was as follows: self-fulfillment, interpersonal relationships, nutrition, stress management, health responsibility and physical activity [25]. In a study conducted in nursing students in the United States of America, the highest scores were in interpersonal relations and self-fulfillment sub-dimensions while the lowest score was in health responsibility [26]. The reason that self-fulfillment sub-scale gets the first place is thought to be influenced by societal and personal beliefs while the reason for the exercise sub-scale taking the last place is thought to be a lack of full understanding of sports culture in society, the costs of gyms, living conditions in the society in general and lack of time as a result of this, not having alternative sport fields at the desired level.…”
Section: In Terms Of Average Healthy Life Style Behavior Scale Subscamentioning
confidence: 99%
“…Although the correlation between the effects of the nursing courses on the HPLP have been confirmed by other studies (Duffy et al, 1996), the integration of health promotion within nursing curricula is crucial to facilitate the transfer of theoretical concepts into practice (Benson & Latter, 1998). As suggested by Stark et al (2005), students' self-care strategies might improve with integration in a nursing course. Wilsgaard et al (2005) assessed the rela-tionships between lifestyle factors and the BMI in a longitudinal study and found most relationships strengthened over time.…”
Section: Discussionmentioning
confidence: 89%
“…The current body of evidence suggests that many university students adopt unhealthy lifestyle behavior as a result of a range of individual, social, and environmental factors, and nursing students might be at risk of poorer health behavior and dietary patterns due to the additional pressures of clinical placement and clinical experiences associated with caring for others. Existing evidence supports the provision of healthy eating interventions for university students (Martinez et al, 2016;Sogari et al, 2018) and including self-care education in nurses' curriculum (Horneffer, 2006;Stark et al, 2005). Therefore, the development of healthier dietary behavior in nurses may help to address issues with student dropout and retention in the nursing workforce and support nurses to establish and maintain healthier lifestyles and work as positive role models to their patients.…”
Section: Study Aimmentioning
confidence: 99%